2003
DOI: 10.1002/cncr.11196
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mitotic rate is a more powerful prognostic indicator than ulceration in patients with primary cutaneous melanoma

Abstract: BACKGROUNDThe current study was performed to determine whether tumor mitotic rate (TMR) is a useful, independent prognostic factor in patients with localized cutaneous melanoma.METHODSFrom the Sydney Melanoma Unit database, 3661 patients with complete clinical information and details of primary tumor thickness, ulcerative state, and TMR were studied. TMR was expressed as mitoses per mm2 in the dermal part of the tumor in which most mitoses were seen, as recommended in the 1982 revision of the 1972 Sydney class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
219
1
21

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(256 citation statements)
references
References 28 publications
15
219
1
21
Order By: Relevance
“…Another study also reported that high mitotic rate (per mm 2 ) was associated with poor prognosis and an important independent predictive factor of survival (Azzola et al, 2003). However, some authors stated that the mitotic rate was not an independent prognostic factor because it was significantly associated with tumor thickness and ulceration (Weedon, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also reported that high mitotic rate (per mm 2 ) was associated with poor prognosis and an important independent predictive factor of survival (Azzola et al, 2003). However, some authors stated that the mitotic rate was not an independent prognostic factor because it was significantly associated with tumor thickness and ulceration (Weedon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ulceration changes in the stage of TNM classification. Ulceration is regarded as an independent prognostic factor for melanoma (Ivan and Prieto, 2011); yet, some authors have not identified ulceration as an independently significant prognostic attribute (Azzola et al, 2003, Uysal-Sonmez et al, 2013, Wu et al, 2013. In addition, another study found that ulceration of the primary lesion was significantly associated with nodal disease on univariate, but not on multivariate analysis (Fontaine et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…25 In determining how the tumor mitotic rate should be categorized, it was established that the prognostic significance of the mitotic rate was strongest when comparing patients who had 0 mitoses/mm 2 and those who had !1 mitosis/mm 2 rather than grouping together patients with 0 mitoses/mm 2 and 1 mitosis/mm 2 . 25,32 The method by which the mitotic rate is measured also affects its utility as a prognostic indicator, and the current recommendation is to use the ''hotspot'' method (recording the highest total number of mitoses/mm 2 ) when evaluating the presence of mitotic figures as opposed to the alternative method of recording the mitoses per high-power field (HPF). 30,33 We analyzed the tumor mitotic rate recorded in our clinicopathologic melanoma database by its absence (0 mitoses/mm 2 or per HPF) or presence (!1 mitosis/mm 2 or per HPF).…”
Section: Discussionmentioning
confidence: 99%
“…61 A mitotic rate of 1 or more per square millimeter was associated with a significant reduction in survivorship, 61 although in this data step-wise increases in mitotic activity did not show significant proportionate reduction in survival. 62 The Philadelphia group has shown a 10-year metastatic rate in men with vertical growth phase melanoma of 31% when a mitotic rate of greater than 0 was identified, vs a 4% mortality rate when the mitotic rate was 0. 63 Barnhill et al 58 studied the impact of mitotic rate upon survival for 650 consecutive primary cutaneous melanoma patients in a logistic regression model.…”
Section: Mitotic Ratementioning
confidence: 99%